Principal's Leadership Style in Facing the Modern World from the Educational Sociology Perspective at State Elementary School 007 Sangatta Utara - Yasin, Muhammad (Lembaga Pendidikan Hikmatun Najah Blora, 2022)
The purpose of this study is to determine the leadership style of school principals in dealing with the modern world from the perspective of the sociology of education, the benefits of this research are beneficial as a reference for principal school leadership to prepare agents of educational change in the face of today's modern world. Modern times all definitely need challenges in the world of education, education must be able to adapt and carry out transformations to keep up with the times, the research used is qualitative research with a descriptive approach, researchers explore data through interviews, with school principals and teachers as well as community members who live in the environment. State Elementary School 007 Sangatta Utara, East Kutai Regency, and from the documentation, the researcher then analyzed the data following the miles style, then by reducing the data after the interview so that less relevant information could be filtered out to near perfection after data reduction then drew conclusions. The findings from the researchers show that there is still a lack of principals in following technological developments, plus the facilities are still inadequate, ideally in schools having 25 computers or laptops and schools do not yet have a computer lab to support school programs so that the program does not run optimally. The principal is very important and must master technology to make it easier for education personnel to control.